Shelf versus Traditional Seasoned Equity Offerings: The Impact of Potential Short Selling - Dutordoir, Marie; Strong, Norman; Sun, Ping (Journal of Financial and Quantitative Analysis, 2019)
Traditional seasoned equity offerings (SEOs) elicit short selling from traders trying to increase offering discounts. Such short selling is more difficult for shelf offerings because the time between their announcement and issuance tends to be shorter. We predict and find that firms with higher short-selling potential (SSP) are more likely to choose shelf over traditional SEOs. This result is robust to alternative proxies for SSP and other sensitivity tests. Further analysis suggests that shelf issuers aim to mitigate the threat of manipulative short selling. Our findings add to a growing literature showing that short selling has a real impact on corporate finance decisions.